The Eff ects of CTBN on Mechanical and Viscoelastic Viscosity Properties of Epoxy-Silica Nanocomposites - Raja Nor Izawati Raja Othman; Nor Hasyidah Mohd Sakeri (Penerbit Universiti Kebangsaan Malaysia, 2025)
Epoxy resin demonstrates remarkable adhesion, mechanical properties, and heat resistance, however, its inherent brittleness warrants attention. Therefore, hybrid composite was prepared using epoxy resin as the polymer matrix, with carboxyl- terminated butadiene nitrile liquid rubber (CTBN), and nanosilica as the reinforcement materials to increase the mechanical properties. The loading for CTBN and nanosilica are set to (5 wt.%, 10 wt.%, 15 wt.% and 20 wt.%); and (1 wt.%, 2 wt.%, 3 wt.% and 4 wt %.); respectively. The epoxy composites are toughened by adding various loadings of CTBN. Then, fracture toughness and viscoelastic viscosity properties of the composites are measured. At 15 wt.% of CTBN loading, nanosilica are added at different loadings to examine the improvement of composites. Then, fracture toughness (KIC), the glass transition temperature (Tg), loss modulus (E”) and storage modulus (E’) were all measured. Incorporating CTBN into epoxy matrix improves fracture toughness up to 79.4%, with optimum loading of 15 wt.%. Nanosilica content also significantly impacts fracture toughness, with a maximum enhancement of 107.7% at 3 wt.% loading. The glass transition temperature increases with CTBN content, reaching 17.01% improvement at 15 wt.% loading and 18.32% improvement at 20 wt.% loading. Nanosilica is also found to increase glass transition temperature, reaching 74.49°C, at 3 wt.% loading and 83.33°C, at 4 wt.%. The loss modulus increases as CTBN and nanosilica loading increases. At a loading of 20 wt.% CTBN, it reaches a maximum value of up to 164.7%. Adding further 4 wt.% nanosilica to 20 wt.% CTBN, resulted in an increase in loss modulus up to 1600%. The storage modulus also increases as CTBN and nanosilica loading increases to 20 wt.% and 4wt.%, respectively and it reached 1662% from neat epoxy. In conclusion, a combination of 15 wt.% CTBN and nanosilica have increased the fracture toughness and viscoelastic viscosity properties of epoxy composites. .